Cele regulacji w ochronie środowiska a podatki ekologiczne - Borys, Grażyna (Goals of regulations in environment protection vs. ecological taxes, 2005)
The objective of the hereby article is to provide an analysis of the problem whether ecological taxes are capable of meeting basic goals of regulations in environment protection. Among such goals there are the following: ecological effectiveness, static and dynamic efficiency, flexibility, compatibility with the existing forms of regulations and political feasibility.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 11-17